Strategies to improve the medical device life cycle in Mexico - Myriam Lingg; Anahi Dreser; Luis Durán-Arenas; Kaspar Wyss (Instituto Nacional de Salud Pública, 2018)
Objective. To analyze the role of stakeholders to three alternative strategies to improve processes and practices regarding the regulation, assessment, and management oforthopaedic medical devices in Mexico. Materials and methods. The study was based on document analysis and 17 structured interviews with multiple key actors within the Mexican health system to inform a stakeholder analysis aiming at assessing the political feasibility of these strategies. Results. Central level government agencies, those with a relation to quality of care, were identified as most relevant stakeholders to influence the adaption and application of the strategies. Major barriers identified are financial and human resources, and organisational culture towards reform. Conclusion. Discussed strategies are political feasible. However, solving identified barriers is crucial to achieve changes directed to improve outputs and outcomes of medical device life cycle and positively influence the quality of health care and the health system's performance.